The politics of expertise and ignorance in the field of migration management. (August 2019) - Scheel, Stephan; Ustek-Spilda, Funda
This paper shows that the field of migration management features a politics of expertise through which migration is enacted as a reality that can be managed because it can be precisely quantified. For instance, the International Organization for Migration maintains a "Global Migration Flows Interactive App." This interactive map suggests that the number of people migrating from country A to B can be exactly known at any point in time. This enactment of migration sits in contrast with the widely acknowledged unreliability and noncoherence of migration statistics. This paper investigates how this tension is negotiated through the production of "strategic ignorance" (McGoey) about the known limits of quantifying migration. Drawing on work from ignorance studies we highlight four practices producing strategic ignorance: (1) omission of the significant gap between recorded immigration and emigration events, (2) compression of different accounts of migration into one "world migration map, " (3) deflection of knowledge about the specifities of different methods to production sites of statistical data, and (4) usage of metadata for sanitizing the statistical production process of any messy aspects. Our analysis shows that the politics of expertise in the field of migration management are intertwined with a politics of ignorance.